Spontaneous intracerebral hemorrhage treated by neuroendoscopy: technical note - Romero, Flavio Ramalho [UNESP]; Zanini, Marco Antônio [UNESP]; Ducati, Luiz Gustavo [UNESP]; Gabarra, Roberto Colichio [UNESP] (My University, 2013)
Spontaneous intracerebral hemorrhage (SICH) is responsible for 10%-15% of the acute stroke. Hematoma or the occlusion of cerebrospinal fluid (CSF) flow by ventricular clotting can result in obstructive hydrocephalus, increasing intracranial pressure, which needs urgent decompression. We report our results of management of spontaneous deep cerebral hematoma by endoscopic approach.

Hematoma intracerebral espontâneo tratado por neuroendoscopia – Nota técnica Hemorragia intracerebral espontânea é responsável por 10%-15% dos acidentes vasculares encefálicos agudos. Hematoma ou a oclusão da drenagem de liquor por coágulo sanguíneo pode resultar em hidrocefalia, aumentando a pressão intracraniana, com necessidade de tratamento de emergência. Relatamos nossa técnica na abordagem do hematoma cerebral profundo por neuroendoscopia.
Keywords: Intracranial hemorrhages; Neuroendoscopy; Stroke; Hemorragias intracranianas; Neuroendoscopia; Acidente vascular cerebral